Strategi Pemasaran Media Sosial Pada Produk ‘’Indomie” Dalam Membangun Brand Awarness - Nahdya Alfaina Karem; Sulistyowati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A Social Media Marketing Strategy is a detailed plan designed to utilize social media platforms in achieving specific business goals. It includes various activities aimed at increasing engagement, building relationships with consumers, and promoting products or services. This research uses qualitative descriptive research methods. In this case, the strategy that can be done is through interesting creative content, direct interaction, and the use of paid advertisements on platforms such as Facebook, Instagram, and Twitter. This strategy has several main objectives, one of which is to build brand awareness. Likewise, the social media marketing strategy carried out by “Indomie” products in building brand awareness so that its products can be recognized and remembered by consumers. In building brand awareness “indomie” has done so by creating a distinctive jingle for this brand, namely “indomie my taste”, because the jingle advertised through social media such as tv, instragam, tiktok, etc. is judged to make consumers recognize and remember this product.